Innovation in environmental governance in the City of São Paulo: Implementation of linear parks. - Silva-Sánchez, Solange; Jacobi, Pedro R. (Routledge, 2013)
As part of the directives featured in its 2002 municipal master plan, the Brazilian city of São Paulo has drafted an innovative policy for recovering its urban rivers and streams. This policy represents a new paradigm for the city in terms of its relationship to the many rivers and streams that have been buried under roads and expressways. This article shows that the creation of riverside parks, an important element of the plan, have been recognized by São Paulo's citizens as a genuine contribution to improving the quality of urban life.
Keywords: Großstadt; Freiraumplanung; Fluss; Park; Grünfläche; Stadtraum; Stadtökologie; Stadtpark; Linearer Park; Masterplan